Assessing the role of online mathematics tools in enhancing student learning and engagement - Olajumoke Olayemi Salami; Erica Dorethea Spangenberg (Educational Technology Quarterly)
As digital technology improves and educational standards rise, online tools for teaching mathematics are one of the advancements recorded in digital technologies. The use of digital tools for teaching, particularly a dreaded subject like mathematics, helps to improve teaching and learning. This study explores the influence of online learning tools on the teaching of mathematics in the era of the Fourth Industrial Revolution (4IR), where the fusion of digital, physical, and biological spheres is revolutionising conventional education practices. In this study, a survey of 596 secondary school mathematics educators was administered to evaluate the correlation between online tool use and student performance through correlation analysis and multinomial logistic regression. Results showed a strong positive relationship between the use of online resources and student engagement, problem-solving, and academic achievements. The study calls for focused professional development and training activities to provide teachers with the knowledge and skills needed to use online resources in their classrooms. In addition, government and education stakeholders should invest in infrastructure to enable fair access to digital learning resources so that a sizable number of teachers and students can take advantage of technology-rich education.